PERLINDUNGAN ANAK DARI EKSPLOITASI EKONOMI DI YAYASAN PANTI ASUHAN: PERSPEKTIF HUKUM PERLINDUNGAN ANAK - Aldy Arveransyah; Diding Rahmat (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2025)
In discussions of children's rights, the economic exploitation of children in orphanages is often overlooked. This exploitation can take various forms, such as exploiting children for financially disadvantageous work that they cannot afford, or exploiting them for work that is harmful to their physical or mental health. The purpose of this study is to determine the types of economic exploitation occurring in orphanages and analyze how it impacts children's rights from the perspective of Indonesian child protection law. This study uses normative juridical approaches, namely prescriptive and comparative legal analysis. This study finds that economic exploitation in orphanages often violates basic principles of child protection, such as the right to education, the right to adequate care, and the right to adequate care. This is demonstrated by related regulations, such as Minister of Social Affairs Regulation No. 30 of 2011 concerning National Standards for Child Care. In addition, this study examines the provisions of the Convention on the Rights of the Child (CRC), adopted by Indonesia through Presidential Decree No. 36 of 1990, with other international regulations. Studies show that, although Indonesian law has established clear regulations on child protection, weak supervision and enforcement result in many orphanages not complying with these regulations. This study recommends increased oversight of orphanages and tougher penalties for child economic exploitation. It is hoped that this research will help develop better and more sustainable child protection policies in Indonesia.